2014
DOI: 10.2139/ssrn.2217500
|View full text |Cite
|
Sign up to set email alerts
|

Margins, Gravity, and Causality: Export Diversification and Income Levels Reconsidered

Abstract: The paper shows that the relationship between GDP per capita and levels of specialization can be predicted differently depending on whether the intensive or the extensive margin is considered. It shows that at the extensive margin countries continuously diversify their exports and that cross-sectional patterns can be captured well by a gravity equation. Prior studies documenting nonmonotone patterns with respecialization appear to have obtained their results from sample-selection bias, the omitted log-transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 35 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…The country's foreign economic indicators are a significant export factor. The openness of the economy has a positive effect on the volume of exports (see, for example, the works of Parteka & Tamberi [14] and Mau [15]). Based on data on 175 countries from 1980 to 2007, Iwamoto & Nabeshima [16] showed that foreign direct investment (FDI) leads to export diversification.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The country's foreign economic indicators are a significant export factor. The openness of the economy has a positive effect on the volume of exports (see, for example, the works of Parteka & Tamberi [14] and Mau [15]). Based on data on 175 countries from 1980 to 2007, Iwamoto & Nabeshima [16] showed that foreign direct investment (FDI) leads to export diversification.…”
Section: Literature Reviewmentioning
confidence: 99%